2012
DOI: 10.1111/j.1365-2702.2011.03943.x
|View full text |Cite
|
Sign up to set email alerts
|

Communication between nurses, children and their parents in asthma review consultations

Abstract: Communication is an essential component of children's asthma care. Guidance encourages practitioners to use review consultations to help children and parents to identify areas where they want treatment to have effect and to negotiate personalised action plans with practitioners. There is potential for conflict as well as cooperation. There is a need for more research into nurses' communication with children and parents to provide an evidence base for practice, education and training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(65 citation statements)
references
References 12 publications
2
62
0
1
Order By: Relevance
“…Findings here support Buford's (2005) study, which found that not only did children want information, but they expected this information to come directly from health professionals. Parents believe that it is important for health professionals to communicate directly with children (Buford, 2005;Callery and Milnes, 2012). Yet, in support of other studies Lambert et al 349 (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Findings here support Buford's (2005) study, which found that not only did children want information, but they expected this information to come directly from health professionals. Parents believe that it is important for health professionals to communicate directly with children (Buford, 2005;Callery and Milnes, 2012). Yet, in support of other studies Lambert et al 349 (e.g.…”
mentioning
confidence: 99%
“…The standard development process could help clarify each cohort's expectations of each other in relation to information giving/receiving and resolve role ambiguity in the information exchange process. Support for this recommendation is heightened by Callery and Milnes's (2012) revelation that the negotiation of roles in parent-child-nurse interactions was not discussed and consequently conflicts arose over different beliefs about what role children, parents and practitioners should assume.…”
mentioning
confidence: 99%
“…This process relies upon and develops the unity between nurse and consumer; unity refers to interpersonal dynamics and harmony, and the mutual motivation and commitment to achieve agreed upon goals. An effective nursing alliance involves such a process and unity (Callery & Milnes, 2012;Cole, 2006;Doherty, 2009;Gardner, 2010;Madden, 1990;Shattell, Starr, & Thomas, 2007 & Wood, 2010). The term 'partnership' symbolises the process and unity of a therapeutic alliance, representing equality, mutual agreement, collaboration and interpersonal engagement (Conway, 1998;Hostick & McClelland, 2002;Shanley & Jubb-Shanley, 2007;Shanley & Jubb-Shanley, 2012;Surtees, 2007).…”
Section: Partnershipmentioning
confidence: 95%
“…This collaborative process requires that the power and influence that a nurse maintains in a relationship is carefully directed to facilitate the consumer leading their own recovery (Shattell et al, 2007;Spiers & Wood, 2010). Empowerment also involves the mobilisation of resources and inner strengths of the consumer, such as interventions which involve the consumer's family or the provision of other services, such as psychoeducation and skills training (Callery & Milnes, 2012;Doherty, 2010;Dubyna & Quinn, 1996;Radcliffe, Adeshokan, Thompson, & Bakowski, 2012;Sturis, 2002).…”
Section: Consumer Empowermentmentioning
confidence: 99%
See 1 more Smart Citation